Effects of relative humidity on aerosol light scattering: results from different European sites - P. Zieger; R. Fierz-Schmidhauser; E. Weingartner; U. Baltensperger (Atmospheric Chemistry and Physics, 2013)
The effect of aerosol water uptake on the aerosol particle light scattering coefficient (σsp) is described in this study by comparing measurements from five European sites: the Jungfraujoch, located in the Swiss Alps at 3580 m a.s.l.; Ny-Ålesund, located on Spitsbergen in the Arctic; Mace Head, a coastal site in Ireland; Cabauw, a rural site in the Netherlands; and Melpitz, a regional background site in Eastern Germany. These sites were selected according to the aerosol type usually encountered at that location. The scattering enhancement factor f(RH, λ) is the key parameter to describe the effect of water uptake on the particle light scattering. It is defined as the σsp(RH) at a certain relative humidity (RH) and wavelength λ divided by its dry value. f(RH) at the five sites varied widely, starting at very low values of f(RH = 85%, λ = 550 nm) around 1.28 for mineral dust, and reaching up to 3.41 for Arctic aerosol. Hysteresis behavior was observed at all sites except at the Jungfraujoch (due to the absence of sea salt). Closure studies and Mie simulations showed that both size and chemical composition determine the magnitude of f(RH). Both parameters are also needed to successfully predict f(RH). Finally, the measurement results were compared to the widely used aerosol model, OPAC (Hess et al., 1998). Significant discrepancies were seen, especially at intermediate RH ranges; these were mainly attributed to inappropriate implementation of hygroscopic growth in the OPAC model. Replacement of the hygroscopic growth with values from the recent literature resulted in a clear improvement of the OPAC model.